Water quality degradation processes and driving mechanisms in typical macrophytic lakes of the Yangtze River mid-lower reaches: a case study of East Taihu Lake and Liangzi Lake - Liu, Jinliang; Zou, Wei; Li, Shuaidong; Wang, Xiaolei; Gu, Xiaoli; Chen, Sophia Shuang; Fei, Chenxi (Frontiers in Ecology and Evolution, 2025)
Water quality degradation threatens macrophyte-dominated lake ecosystems, necessitating systematic analysis of spatiotemporal patterns and anthropogenic drivers. This study examines two macrophytic lakes (East Taihu and Liangzi Lake) using water quality monitoring data (2005–2023) through trophic state index (TSI), comprehensive pollution index (Pw), and dynamic change analyses. The results reveal divergent trends: East Taihu Lake exhibited an increase in chlorophyll α, total phosphorus (TP), and ammonia-nitrogen (NH3-N), while total nitrogen (TN), permanganate index (CODMn), and secchi depth (SD) exhibited a decline. Prior to 2018, the TSI and Pw of East Taihu Lake exhibited an upward trend; however, after 2018, they demonstrated a gradual decline. Notably, the TSI of East Taihu Lake persists at a relatively elevated level (TSI > 50), thus being classified as eutrophic, with TP identified as the predominant contributor to water pollution (p< 0.01). All water quality indexes, TSI, and Pw of Liangzi Lake have shown an upward trend, but its TSI and Pw are lower than those of East Taihu Lake, being mesotrophic (30< TSI< 50), but in some stages it is close to eutrophic. CODMn and TP dominated Liangzi’s pollution (p< 0.01). Correlation analyses have identified intensive anthropogenic activities, including population growth, agricultural/industrial expansion, fertilizer/pesticide use, wastewater discharge, and cage aquaculture expansion – as key drivers of water quality deterioration. Meanwhile, the increase in nutrient concentrations and the outbreak of cyanobacterial blooms caused by the release of endogenous pollutants should not be overlooked. Effective restoration requires integrated strategies. These include: 1) controlling external pollutant loads, especially phosphorus inputs, 2) optimizing aquatic vegetation and fish communities, and 3) strengthening lake management regulations. These measures are essential for the restoration of the clear and stable state of macrophyte-dominated lakes.